Anales 2015: Perspectives of the San Fernando School of Medicine journal - Vildózola Gonzáles, Herman (2015)
Anales de la Facultad de Medicina appeared as the School of Medicine journal 97 years ago, and following some years of absence, has been published both physically and virtually for the past 20 years. The important indizations obtained is a challenge to consider publishing in the near future all articles in English language, increasing the journal periodicity to every two months, implement a multinational Advisory Committee, and to increase the finantial support to Anales.